Bifunctional nano-catalyst produced from palm kernel shell via hydrothermal-assisted carbonization for biodiesel production from waste cooking oil - Abdullah, Rose Fadzilah; Rashid, Umer; Ibrahim, Mohd Lokman; Hazmi, Balkis; Alharthi, Fahad A.; Nehdi, Imededdine Arbi (Elsevier, 2021)
A highly mesoporous activated carbon derived from palm kernel shell was successfully prepared by hydrothermal-assisted carbonization (HTC) by improving the degradation of lignocellulosic composition and increase the porous texture of carbon structure. Additional NaOH treatment increased the surface area of the catalyst which enhanced the loading of the active site. Further impregnation of HTC based activated carbon with K2CO3 and CuO via wet impregnation provided bifunctional characteristics suitable for simultaneous esterification and transesterification processes. The physicochemical properties of the prepared catalysts were conducted through the state-of-the-art techniques including N2 adsorption-desorption analysis, functional group determination, surface morphology study, electron dispersive x-ray mapping, elemental distribution analysis, amount of basicity and acidity strength and thermal degradation behavior analysis. The investigation found that the chemical treatment with NaOH significantly increased the surface area from 3.57 to 3368.60 m2/g and impregnation with K2CO3 and CuO offered higher amount of basicity of 5.73 mmol/g and acidity of 1.48 mmol/g, respectively. These properties enhanced the simultaneous esterification-transesterification of waste cooking oil to biodiesel. The catalytic study produced 95.36 ± 1.4% of biodiesel over 4 wt% of PKSHAC-K2CO3(20%)CuO(5%) catalyst, 12:1 of methanol to oil molar ratio, reaction temperature of 70 °C for duration of 2 h. Meanwhile, the catalyst can be employed for five subsequent reaction cycles with FAME yield of 82.5 ± 2.5%. Thus, the synthesized bifunctional nanocatalyst supported on the HTC based activated carbon has been validated as an efficient catalyst for biodiesel production.